(untitled) (Groundings Undergraduate, 2024)
This paper investigates the development of Abstract Expressionism in 1940-1950s America, focusing on ways it has been constructed as a masculine form of expression. Emerging after the end of WW2 when the American national identity was being re-defined, the art movement became a site for the interplay of multiple socio-political and cultural tensions. The imposition of qualities traditionally associated with masculinity became a key aspect in the reception of the movement, reflecting the interests of multiple institutions. This paper deconstructs the amalgamation of factors that formed the masculine image of Abstract Expressionism. These factors range from the masculinising language of art critics such as Clement Greenberg to America’s Cold War agenda to male artists’ own internalisation of philosophical ideas that projected the movement’s masculine aura. In the last section of my investigation, I will expose the gendered imbalance within Abstract Expressionism by analysing the contrast in the occupation of space by male and female artists in period photographs.